Metformin Promotes Mechanical Stretch-Induced Skin Regeneration by Improving the Proliferative Activity of Skin-Derived Stem Cells - Xiong, Shaoheng; Liu, Wei; Song, Yajuan; Du, Jing; Wang, Tong; Zhang, Yu; Huang, Zhaosong; He, Qiang; Dong, Chen; Yu, Zhou; Ma, Xianjie (Frontiers in Medicine, 2022)
Background: Skin expansion by mechanical stretch is an essential and widely used treatment for tissue defects in plastic and reconstructive surgery; however, the regenerative capacity of mechanically stretched skin limits clinical treatment results. Here, we propose a strategy to enhance the regenerative ability of mechanically stretched skin by topical application of metformin. Methods: We established a mechanically stretched scalp model in male rats (n = 20), followed by their random division into two groups: metformin-treated (n=10) and control (n=10) groups. We measured skin thickness, collagen volume fraction, cell proliferation, and angiogenesis to analyze the effects of topical metformin on mechanically stretched skin, and immunofluorescence staining was performed to determine the contents of epidermal stem cells and hair follicle bulge stem cells in mechanically stretched skin. Western blot was performed to detect the protein expression of skin-derived stem cell markers. Results: Compared with the control group, metformin treatment was beneficial to mechanical stretch-induced skin regeneration by increasing the thicknesses of epidermis (57.27 ± 10.24 vs 31.07 ± 9.06 μm, p < 0.01) and dermis (620.2 ± 86.17 vs 402.1 ± 22.46 μm, p < 0.01), number of blood vessels (38.30 ±6.90 vs 17.00 ± 3.10, p < 0.01), dermal collagen volume fraction (60.48 ± 4.47% vs 41.28 ± 4.14%, p < 0.01), and number of PCNA+, Aurora B+, and pH3+ cells. Additionally, we observed significant elevations in the number of proliferating hair follicle bulge stem cells [cytokeratin (CK)15+/proliferating cell nuclear antigen (PCNA)+] (193.40 ± 35.31 vs. 98.25 ± 23.47, p < 0.01) and epidermal stem cells (CK14+/PCNA+) (83.00 ± 2.38 vs. 36.38 ± 8.96, p < 0.01) in the metformin-treated group, and western blot results confirmed significant increases in CK14 and CK15 expression following metformin treatment. Conclusion: Topical application of metformin enhanced the regenerative capacity of mechanically stretched skin, with the underlying mechanism possibly attributed to improvements in the proliferative activity of skin-derived stem cells.